2003
DOI: 10.2741/1142
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of adynamia in aphasia

Abstract: Transcortical motor aphasia (TCMA) is an acquired impairment of language expression that occurs following neurologic damage that affects left frontal cortex and spares perisylvian regions. In some individuals with TCMA, verbal expression is rendered nonfluent due to difficulty spontaneously initiating and elaborating upon verbal messages. Nonfluency arises from impaired activation of intended messages and inhibition of competing verbal expressions. This impairment of the intentional aspects of language express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
0
8
1
2
Order By: Relevance
“…Beneficial changes were noted in speech initiation, pauses in conversation, paraphasias, and naming, with these attributed to enhanced dopaminergic tone in the mesocortical pathway (Albert et al 1988). These findings were replicated in other single cases and open-label trials of transcortical motor, adynamic, and Broca's aphasias of moderate severity (Berthier 1999(Berthier , 2005Raymer et al 2001;Raymer 2003), but not in cases with severe Broca's and global aphasias (Gupta and Mlcoch 1992;Sabe et al 1992;Ozeren et al 1995). Moreover, the beneficial effects found in selected single cases and open-label studies were not confirmed in most randomized controlled trials (Gupta et al 1995;Ozeren et al 1995;Sabe et al 1995;Ashtary et al 2006).…”
Section: Catecholaminergic Drugscontrasting
confidence: 51%
“…Beneficial changes were noted in speech initiation, pauses in conversation, paraphasias, and naming, with these attributed to enhanced dopaminergic tone in the mesocortical pathway (Albert et al 1988). These findings were replicated in other single cases and open-label trials of transcortical motor, adynamic, and Broca's aphasias of moderate severity (Berthier 1999(Berthier , 2005Raymer et al 2001;Raymer 2003), but not in cases with severe Broca's and global aphasias (Gupta and Mlcoch 1992;Sabe et al 1992;Ozeren et al 1995). Moreover, the beneficial effects found in selected single cases and open-label studies were not confirmed in most randomized controlled trials (Gupta et al 1995;Ozeren et al 1995;Sabe et al 1995;Ashtary et al 2006).…”
Section: Catecholaminergic Drugscontrasting
confidence: 51%
“…Solo unas pocas intervenciones de corte conductual han sido propuestas para mejorar la capacidad de iniciar la expresión verbal espontánea, que supone la participación de regiones frontales intactas (22). Algunos datos sugieren que los movimientos no simbólicos concomitantes a la producción oral, como una forma de lo que denomina Luria reorganización gestual, puede mejorar la expresión verbal adinámica.…”
Section: Discussionunclassified
“…También se reporta en la literatura, el efecto del tratamiento farmacológico con bromocriptina, un agonista dopaminérgico, en formas de afasia no fluidas; en particular, los individuos clasificados con ATM tienen más probabilidades de beneficiarse de la farmacoterapia de aquellos que tienen otras formas de afasia no fluente, lo que sugiere una influencia de la bromocriptina en los circuitos necesarios para activar el lenguaje espontáneo (23). No obstante, se señala que las intervenciones farmacológicas en conjunto con las de tipo conductual mejoran la expresión verbal en mayor medida en que lo hace la farmacoterapia cuando se usa como úni-ca opción terapéutica (22). La documentación acerca de la cantidad, proporción y desenlaces de la recuperación de los desórdenes neurocomunicativos, demuestra que es muy difícil predecir a largo plazo la funcionalidad de un paciente con daño cerebral.…”
Section: Discussionunclassified
“…Among all, bromocriptine agonist of postsynaptic dopamine D2 receptor has been investigated more than others (7,21,23 Ramezani S, et al that the type of aphasia (22,23), the cause of aphasia (98), the treatment plan (99) and dose of medication (100) play a vital role in outcome. Bromocriptine functions on mesocortical dopaminergic neurons which project from mesencephalon to dorsal caudate nucleus of basal gangalia, supplementary motor area (SMA) and anterior cingulum (101).…”
Section: Drugs Acting On Catecholaminergic Systemmentioning
confidence: 99%
“…Much effort have been put on aphasia pharmacotherapy in past half century particularly revealing conflicting results on dopaminergic agonists. Dopaminergic drugs if taken along with aphasia therapy would be effective in patients with mild to moderate fluent aphasia, though not expected in other conditions (7,(21)(22)(23)(24). The recent two decades has seen accelerated developments in neuroscience research in favor of pharmacotherapy to improve the language deficits (8).…”
Section: Introductionmentioning
confidence: 99%